2002
DOI: 10.1016/s0002-9440(10)61125-x
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of Transforming Growth Factor-β1 by Pancreatic Stellate Cells and Its Implications for Matrix Secretion and Turnover in Chronic Pancreatitis

Abstract: Pancreatic stellate cells mediate fibrosis in chronic pancreatitis. Matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs)-1 and -2 are crucial modulators of fibrosis. Transforming growth factor-beta (TGF-beta) is a key regulator of extracellular matrix production and myofibroblast proliferation. We have examined MMP and TIMP synthesis by transformed cultured pancreatic stellate cells and their regulation by TGF-beta 1. By Northern analysis they expressed mRNAs for procollagen 1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
214
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 267 publications
(231 citation statements)
references
References 40 publications
7
214
0
4
Order By: Relevance
“…TGFb1 did not only induce the expression of ECM components Col I and FN, but also of the growth factors CTGF and TGFb1 itself, thus establishing an autocrine loop, which may result in the perpetuation of the fibrotic process. This autocrine stimulation of PSC was also demonstrated by Shek et al 47 pinpointing the central role PSC play in the development of pancreatic fibrosis. Taken together, the immortalized PSC retain the basic characteristics of activated PSC, as expression of marker protein and responsiveness to factors implicated in pancreatic fibrosis.…”
Section: Deactivation Of Pancreatic Stellate Cells R Jesnowski Et Alsupporting
confidence: 69%
See 1 more Smart Citation
“…TGFb1 did not only induce the expression of ECM components Col I and FN, but also of the growth factors CTGF and TGFb1 itself, thus establishing an autocrine loop, which may result in the perpetuation of the fibrotic process. This autocrine stimulation of PSC was also demonstrated by Shek et al 47 pinpointing the central role PSC play in the development of pancreatic fibrosis. Taken together, the immortalized PSC retain the basic characteristics of activated PSC, as expression of marker protein and responsiveness to factors implicated in pancreatic fibrosis.…”
Section: Deactivation Of Pancreatic Stellate Cells R Jesnowski Et Alsupporting
confidence: 69%
“…15,47,48 The same is true for HSC, where contrasting data describing the influence of TGFb1 on proliferation, ranging from growth inhibition to stimulation of proliferation, have been published, although the majority of publications report a TGFb1-induced growth inhibition in HSC. 44,[49][50][51] These differences may be attributed to different RT-PCR demonstrated that cultivation of immortalized PSC on Matrigel (M) for 7 days resulted in a marked decrease of Col I, TGFb1 and CTGF expression compared to cultivation on tissue culture (TC) plates, whereas aSMA expression was not altered significantly by this cultivation conditions, the housekeeping gene RPL13A served as control (a).…”
Section: Deactivation Of Pancreatic Stellate Cells R Jesnowski Et Almentioning
confidence: 98%
“…Studies have shown that TGF-b1 promotes fibrogenesis not only by increasing collagen production but also by inhibiting MMPs in the pathway of collagen degradation. It has been demonstrated by Shek et al [12] that activated PSCs also express activated TGF-b1, which up-regulates collagen-1 while down regulating the expression of MMP-3 and MMP-9 only and not on TIMP-1 expression. The pattern of expression of the mediators studied is similar to that described in parallel cell types of fibrosis of the liver and kidney and reinforces the hypothesis that there may be generic aspects to wound healing in organs [13].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the combination of low expression of collagenases and stromelysins results in the prevention of degradation of the fibrillar collagens deposited due to PSC activation. It is further strengthened by TGF-b1 influencing in decreasing the induction of MMP3 expression [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation